Inhibitory role of dentate hilus neurons in guinea pig hippocampal slice - Müller, Wolfgang; Misgeld, Ulrich (Journal of neurophysiology, 1990)
1. Current and voltage-clamp recording of CA3/CA4 pyramidal neurons, hilar neurons, and granule cells or pairs of these neurons were used to study the generation of Cl-dependent and K-dependent inhibitory postsynaptic potentials (IPSPs) in the guinea pig hippocampal slice preparation. 2. A sequence of an early Cl-dependent and a late K-dependent IPSP was evoked in CA3 neurons by electrical stimulation from the stratum moleculare of the dentate gyrus, the hilus, and the stratum oriens/alveus. Blockade of glutamatergic excitation by 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX, 10 microM) and D(-)-2-amino-5-phosphonovaleric acid (APV, 30 microM) abolished IPSPs evoked from the stratum moleculare of the dentate gyrus, but IPSPs could still be evoked from the hilus and the stratum oriens/alveus. 3. Repetitive giant IPSPs, which consisted of Cl-dependent and K-dependent components, were evoked by bath application of 4-aminopyridine (4-AP, 10-50 microM) in CA3 neurons and in granule cells. Giant IPSPs were blocked by bath-applied tetrodotoxin (TTX). In addition, 4-AP hyperpolarized CA3 neurons in a Cl-dependent and picrotoxin-sensitive way. 4. Focal application of TTX to the dentate gyrus or the hilus considerably reduced the amplitude of giant IPSPs evoked by 4-AP in CA3 neurons. In hilar neurons, 4-AP evoked repetitive bursts, eventually, but not necessarily intermingled with giant IPSPs. Bursts were observed in hilar neurons in presence as well as absence of CNQX and APV. 5. In paired recordings, bursts in hilar neurons induced by 4-AP occurred simultaneously to giant IPSPs in granule cells and CA3 neurons, and giant IPSPs in granule cells occurred simultaneously to giant IPSPs in CA3 neurons. Blockade of glutamatergic excitation by CNQX and APV did not abolish this synchrony. 6. 4-AP-evoked Cl- and K-dependent IPSPs were, unlike electrically evoked IPSPs, not strictly coupled: some 20% of large IPSPs and up to 90% of small IPSPs were either Cl or K dependent. In granule cells K-dependent components either preceded or followed Cl-dependent components. 7. K-dependent IPSPs only could be evoked in CA3 neurons by focal application of 4-AP (1 mM) to the hilus, the stratum lacunosum moleculare or the stratum pyramidale. Wash out of Ca for 15-20 min blocked the Cl-dependent but not the K-dependent component of giant IPSPs evoked by bath-applied 4-AP.(ABSTRACT TRUNCATED AT 400 WORDS)
Gesehen am 08.04.2021